Integration of cell growth and asymmetric division during lateral root initiation in Arabidopsis thaliana - Schütz, Lilli; Louveaux, Marion; Vilches Barro, Amaya; Bouziri, Sami; Cerrone, Lorenzo; Wolny, Adrian; Kreshuk, Anna; Hamprecht, Fred; Maizel, Alexis (Plant & cell physiology, 2021)
Lateral root formation determines to a large extent the ability of plants to forage their environment and thus their growth. In Arabidopsis thaliana and other angiosperms, lateral root initiation requires radial cell expansion and several rounds of anticlinal cell divisions that give rise to a central core of small cells, which express different markers than the larger surrounding cells. These small central cells then switch their plane of divisions to periclinal and give rise to seemingly morphologically similar daughter cells that have different identities and establish the different cell types of the new root. Although the execution of these anticlinal and periclinal divisions is tightly regulated and essential for the correct development of the lateral root, we know little about their geometrical features. Here, we generate a four-dimensional reconstruction of the first stages of lateral root formation and analyze the geometric features of the anticlinal and periclinal divisions. We identify that the periclinal divisions of the small central cells are morphologically dissimilar and asymmetric. We show that mother cell volume is different when looking at anticlinal vs. periclinal divisions and the repeated anticlinal divisions do not lead to reduction in cell volume, although cells are shorter. Finally, we show that cells undergoing a periclinal division are characterized by a strong cell expansion. Our results indicate that cells integrate growth and division to precisely partition their volume upon division during the first two stages of lateral root formation.
Gesehen am 05.01.2022